Cox Regression in Nested Case-Control Studies with Auxiliary Covariates - Liu, Mengling (2009)
Nested case-control (NCC) design is a popular sampling method in large epidemiologic studies for its cost effectiveness to investigate the temporal relationship of diseases with environmental exposures or biological precursors. Thomas’ maximum partial likelihood estimator is commonly used to estimate the regression parameters in Cox’s model for NCC data. In this paper, we consider a situation that failure/censoring information and some crude covariates are available for the entire cohort in addition to NCC data and propose an improved estimator that is asymptotically more efficient than Thomas’ estimator. We adopt a projection approach that, heretofore, has only been employed in situations of random validation sampling and show that it can be well adapted to NCC designs where the sampling scheme is a dynamic process and is not independent for controls. Under certain conditions, consistency and asymptotic normality of the proposed estimator are established and a consistent variance estimator is also developed. Furthermore, a simplified approximate estimator is proposed when the disease is rare. Extensive simulations are conducted to evaluate the finite sample performance of our proposed estimators and to compare the efficiency with Thomas’ estimator and other competing estimators. Moreover, sensitivity analyses are conducted to demonstrate the behavior of the proposed estimator when model assumptions are violated, and we find that the biases are reasonably small in realistic situations. We further demonstrate the proposed method with data from studies on Wilms’ tumor.